Aethetic employment of pop art in television advertising (Al-Academy, 2024)
After the art style of the gatekeeper, Art is one of the methods presented by AL-Musamsim in the desing of television advertisement because of its aesthetics and attractiveness. Each pop art artist had his own style and employed this art in his advertising designs. It is wide, being from your popular life and embodied it in the from of advertisements, in addition to using varios types of materials, ready-made materials, and primary and secondary colors. This research included the methodological framework represented by the problem of the research, the importance of the research, its objectives and limits, and defining the terminology. As for the theoretical framework, it dealt with the aesthetic in the television advertisement, the concept of pop-out and the most prominent pop-artist, as well as the research procedures represented by the research community, the sample, the performance of the out and the most prominent pop-art artist. As well as the research proeduers represedented by the research community, the sample, the performance of the out and the most prominent pop-art artists, as well as the research procedures represented by the research community, the sample, the performance of the research, the analysis of samples, and the results and conclusions that it researcher. Researcher and thereof. 1- The colors used in pop art in the advertisement were achieved through the background of the studio and the brand of the product, so the studio and the brand of the product, so the colors appeared in the snapshot(10,11,1,2,3,4,5,6,7,8,9). 2- The advertising designer deliberately used a new method in the advertisement, and he inserted pop art into the design of the product and tge trademark, as well as background used in advertisement, in order to add a new style in the advertisement and achieve aesthetic and attraction to the viewer, since this art has achieved wide popularity by the community.